2021
DOI: 10.1021/acsami.1c14967
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous TiO2 Bridges Stabilized WS2 Membranes with Excellent Filtration Stability and Photocatalysis-Driving Self-Cleaning Ability

Abstract: Two-dimensional (2D) membranes as a new type of water filtration membrane have shown great potential in water separation and purification. However, their long-term stability under cross-flow conditions and their antifouling property are two main concerns for practical separation and purification processes. In this work, a strategy of nanoparticle bridges based on amorphous TiO2 is developed to link adjacent WS2 nanosheets on a WS2 membrane surface, leading to a strong membrane surface with excellent stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The energy gap between Ti 2p 1/2 and Ti 2p 3/2 is close to 5.8 eV in both WS 2 -TiO 2 and TiO 2 , which is the oxidation state of Ti 4+ . Moreover, Ti 2p 1/2 and Ti 2p 3/2 in WS 2 -TiO 2 are both higher than those in TiO 2 (about 0.3 eV), which is due to the Ti-O-W linkage on the WS 2 -TiO 2 surface by transformation of electrons to WS 2 , which also demonstrates the formation of heterostructures.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The energy gap between Ti 2p 1/2 and Ti 2p 3/2 is close to 5.8 eV in both WS 2 -TiO 2 and TiO 2 , which is the oxidation state of Ti 4+ . Moreover, Ti 2p 1/2 and Ti 2p 3/2 in WS 2 -TiO 2 are both higher than those in TiO 2 (about 0.3 eV), which is due to the Ti-O-W linkage on the WS 2 -TiO 2 surface by transformation of electrons to WS 2 , which also demonstrates the formation of heterostructures.…”
Section: Resultsmentioning
confidence: 93%
“…There are four obvious peaks before and after adsorption in Figure c. Before adsorption of Li 2 S 6 , W 4f 5/2 (34.2 eV) and W 4f 7/2 (32 eV) correspond to W 4+ , and W 4f 5/2 (37.6 eV) and W 4f 7/2 (35.4 eV) correspond to the high state W 6+ , which is jointly attributed to the oxidation of WS 2 on the surface of WS 2 -TiO 2 and the formation of a Ti-O-W bond. , After adsorption of Li 2 S 6 , W 4f 5/2 and W 4f 7/2 peaks move toward the direction of lower binding energy, which proves the existence of electron transfer between Li 2 S 6 and WS 2 Figure d shows the change of S 2p binding energy before and after adsorption of Li 2 S 6 .…”
Section: Resultsmentioning
confidence: 99%
“…Apart from active fouling resistance and release, 2D membranes can be functionalized with photocatalysts to obtain selfcleaning properties; that is, the organic contaminants accumulated on the membrane surface can be degraded when exposed to UV or visible light. A variety of photocatalysts, including titanium dioxide (TiO 2 ), 169,170 graphitic carbon nitride (g-C 3 N 4 ), 171 Fe-based nanomaterials, 172,173 and various heterojunction composites, 174,175 have been integrated into 2D membranes to obtain self-cleaning performance. For instance, the intercalation of g-C 3 N 4 @TiO 2 heterojunctions into lamellar GO membranes enables sunlight-driven self-cleaning properties for the recovery of water flux in practical water/oil separation.…”
Section: Separation-related Rolementioning
confidence: 99%
“…The recently emerging two-dimensional (2D) lamellar membranes based on 2D nanomaterials have attracted a lot of interest due to their outstanding properties and great potential for water treatment. Considerable progresses of 2D membranes reveal a new perspective on advanced membranes in the application of desalination, molecule separation, and ion sieving. 2D membranes are constructed by stacking 2D nanosheets to form a layered structure, and let different ions or molecules selectively permeate through 2D membrane by means of size sieving and interaction between 2D membrane and specific ions or molecules. , Nair and co-workers have reported that GO membranes could block all molecules or ions with hydrated radii larger than 4.5 Å by immersing in water . 2D membranes based on MXene nanosheets effectively excluded molecules with diameters larger than 2.5 nm .…”
Section: Introductionmentioning
confidence: 99%